Accuracy of the combined method (auscultation and pH measurement) and ultrasonography for confirmation of gastric tube placement: a study protocol for a prospective study - Fernanda Raphael Escobar Gimenes; Rosana Aparecida Pereira; Mayara Carvalho Godinho Rigobello; Jorge Elias Junior; Carlos Alberto Grespan Bonacim; Renata Cristina de Campos Pereira Silveira; Fernanda Caroline Bonardi; Roosevelt Santos Nunes (BMJ Open)
Introduction Patients using a nasogastric tube (NGT) are vulnerable to adverse events, therefore proper assessment of these patients, verification of the correct tube placement and constant monitoring by the nursing staff are strategies that can reduce adverse events and risks associated with the care. The aim of this study will be to assess the accuracy of the combined method (auscultation and pH measurement) and ultrasonography for confirmation of gastric tube placement compared with the X-ray method. A further aim will be to measure and provide evidence for the direct costs of each method of confirming NGT placement and to evaluate the impact of each method on the mean direct cost of the patient.Methods and analysis This is a prospective, single-centre study of diagnostic accuracy. Data will be collected in the clinical and surgical wards, intensive care unit and coronary care unit of a Brazilian teaching hospital. The sample will consist of 385 assessments, performed in adult patients that agree to participate in the study and that receive an NGT. The combined method and the ultrasound will be the index tests and will be performed on all study participants for later comparison with an X-ray examination, considered the reference standard and the gold standard to distinguish between gastric and pulmonary placement. Sensitivity, specificity, positive predictive value and negative predictive value will be calculated to assess the diagnostic accuracy of the methods investigated in this study, with Cohen’s kappa analysis used to evaluate the degree of concordance.Ethics and dissemination The study was approved by the Research Ethics Committee of the University of São Paulo at Ribeirão Preto College of Nursing, registration number: 83087318.4.0000.5393. The findings will be reported through academic journals, seminars and conference presentations, social media, print media, the internet and community/stakeholder engagement activities.